New Trends of Islamic Resurgence in Contemporary Malaysia: Sufi-Revivalism, Messianism, and Economic Activism - Hamid, A. Fauzi A. (Studia Islamika, 2014)
This paper, based on research entitled "Islamic Resurgence in the Periphery: A Study of Political Islam in Contemporary Malaysia with Special Reference to the Darul Arqam Movement 1968-1996" (University of Newcastle upon Tyne, 1998), draws upon the systematic, full-blown government repression of Darul Arqam, a sufi revivalist movement, in 1994. The "Darul Arqam challenge" casts a significant light on the various tactics, methods and strategies pursued by Islamic movements in their route to power. This paper recognizes that an analysis of the "Darul Arqam challenge" is incomplete without a consideration of long-term structural processes putting the 1994 events within a broader historical and ideological perspective. Of particular importance is the gradual concoction of a specific organizational and sociopolitical doctrine, concomitant with the execution of a dynamic economic enterprise. It is argued that the elegant combination between theory and practice, in implementing Islam in as comprehensive a manner as possible, serves as the main distinction between Darul Arqam and other contemporary Islamic movements not only in Malaysia but also throughout the ummah. DOI: 10.15408/sdi.v6i3.722